Kedudukan Perempuan Hindu dalam Sistem Pewarisan Menurut Hukum Waris Adat Bali - Firnanda Arifatul Cahyani; Dia Aisa Amelda (Jurnal Hukum Lex Generalis, 2022)
Customary inheritance law is closely related to the kinship system adopted by an indigenous people. Indigenous Balinese adhere to a patrilineal kinship system with a majority inheritance system. So that the heirs in the Balinese customary law community are only boys, while girls are not allowed to inherit. To get her inheritance rights, a Balinese Hindu girl can get it in the form of grants or marriage gifts (spirit of funds), tetadan and bebaktan. Apart from that, it is also possible to change the status of women to men (sentana rajeg).